2019
DOI: 10.1109/tpwrs.2019.2891963
|View full text |Cite
|
Sign up to set email alerts
|

A Statistical Approach to Estimate Imbalance-Induced Energy Losses for Data-Scarce Low Voltage Networks

Abstract: Phase imbalance in the UK and European low voltage (415V, LV) distribution networks causes additional energy losses.A key barrier against understanding the imbalanceinduced energy losses is the absence of high-resolution time-series data for LV networks. It remains a challenge to estimate imbalance-induced energy losses in LV networks that only have the yearly average currents of the three phases. To address this insufficient data challenge, this paper proposes a new customized statistical approach, named as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…W. H. Kersting et al developed a method for computing the currents in the neutral and dirt as well as the associated power losses, which are the consequence of phase unbalance [7]. L. Fang and K. Ma developed a statistical approach to estimate the unbalance-induced energy losses in the neutral and dirt for data-scarce LV networks with data that are only recorded once a year [13]. S. Pajic et al found that for a wide range of conditions, the ratio between the neutral path resistance and the resistance of a transposed three-phase line is approximately given by ≈ ⁄ , where and are the zero and positive sequence resistances of the phase wire, respectively [14].…”
Section: Consequences Of Phase Unbalancementioning
confidence: 99%
See 2 more Smart Citations
“…W. H. Kersting et al developed a method for computing the currents in the neutral and dirt as well as the associated power losses, which are the consequence of phase unbalance [7]. L. Fang and K. Ma developed a statistical approach to estimate the unbalance-induced energy losses in the neutral and dirt for data-scarce LV networks with data that are only recorded once a year [13]. S. Pajic et al found that for a wide range of conditions, the ratio between the neutral path resistance and the resistance of a transposed three-phase line is approximately given by ≈ ⁄ , where and are the zero and positive sequence resistances of the phase wire, respectively [14].…”
Section: Consequences Of Phase Unbalancementioning
confidence: 99%
“…A potential solution is to deploy low-cost monitoring devices at a set of representative LV networks and then use machine learning to extrapolate the knowledge from representative data-rich samples to the vast population of datascarce networks. This type of solution can be applied to identifying customers' phase connectivity [31], the estimation of unbalance-induced energy losses [13], the development of re-phasing guidance [51], etc.…”
Section: Existing Solutions To Phase Unbalancementioning
confidence: 99%
See 1 more Smart Citation
“…W. H. Kersting et al developed a method for computing the currents in the neutral and dirt as well as the associated power losses, which are the consequence of phase imbalance [7]. L. Fang and K. Ma developed a statistical approach to estimate the imbalance-induced energy losses in the neutral and dirt for data-scarce LV networks with data that are only recorded once a year [13]. S. Pajic et al found that for a wide range of conditions, the ratio between the neutral path resistance and the resistance of a transposed three-phase line is approximately given by ≈ ⁄ , where and are the zero and positive sequence resistances of the phase wire, respectively [14].…”
Section: Consequences Of Phase Imbalancementioning
confidence: 99%
“…Even if the three phases of a distribution network were balanced when the network was initially constructed, phase imbalance appears and accumulates over time with loads being added to and removed from each phase. Phase imbalance causes a number of consequences: 1) additional network investment costs because of the inefficient use of network assets [10], [11], [12]; 2) extra energy losses in the transformer, on the phases and neutral, and in the ground [12], [13], [14]; 3) nuisance tripping [15]; and 4) damages to K. Ma, L. Fang, and W. Kong are with the University of Bath, Bath, BA2 7AY, UK (Corresponding author: K. Ma; E-mail: K.Ma@bath.ac.uk).…”
Section: Introductionmentioning
confidence: 99%